2021
DOI: 10.1126/scisignal.aaz2120
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1,4,5-trisphosphate 3-kinase B promotes Ca 2+ mobilization and the inflammatory activity of dendritic cells

Abstract: Innate immune responses to Gram-negative bacteria depend on the recognition of lipopolysaccharide (LPS) by a receptor complex that includes CD14 and TLR4. In dendritic cells (DCs), CD14 enhances the activation not only of TLR4 but also that of the NFAT family of transcription factors, which suppresses cell survival and promotes the production of inflammatory mediators. NFAT activation requires Ca2+ mobilization. In DCs, Ca2+ mobilization in response to LPS depends on phospholipase C γ2 (PLCγ2), which produces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 80 publications
(83 reference statements)
0
20
0
Order By: Relevance
“…The endothelial protective effects of empagliflozin have been described in several in-depth studies. In transverse aortic constriction-induced heart failure, empagliflozin was reported to suppress endothelial apoptosis and maintain capillarization through the Akt/eNOS/nitric oxide pathway, thus increasing heart performance [ 18 , 50 ]. Similarly, empagliflozin was found to inhibit leukocyte-endothelium interactions during diabetes by repressing inflammatory cytokine production [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The endothelial protective effects of empagliflozin have been described in several in-depth studies. In transverse aortic constriction-induced heart failure, empagliflozin was reported to suppress endothelial apoptosis and maintain capillarization through the Akt/eNOS/nitric oxide pathway, thus increasing heart performance [ 18 , 50 ]. Similarly, empagliflozin was found to inhibit leukocyte-endothelium interactions during diabetes by repressing inflammatory cytokine production [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of inflammation, the expression of CD14 proved to be of fundamental importance. Studies performed in murine and human DCs have shown that CD14 triggers crucial inflammatory pathways [13][14][15]. So far, the role of DC3s in inflammation remains to be clarified, as both a pro-and anti-inflammatory role has been described for these cells depending on the disease context [11,12].…”
Section: Subtypes Of Human Dcs: Know Yourselfmentioning
confidence: 99%
“…To further improve selective DC targeting and activation, novel approaches introduced the use of nanoparticles (NPs) as vehicles to deliver viral Ags [15,273] (Figure 3B). Indeed, these carriers constitute in all respects customizable platforms ready to be functionalized and/or encapsulated with everything needed for a focused targeting and activation of DCs.…”
Section: Dc-targeted Vaccines: the Future Is Nowmentioning
confidence: 99%
“…For example, bacterial LPS stimulation of murine DCs induced CD14-dependent extracellular Ca 2+ influx, leading to CN-NFAT activation ( 63 ). Recently, these findings were enriched by a study that showed the importance of inositol triphosphate (IP 3 ) receptor 3 (IP 3 R3) and IP3 kinase B (ITPKB) in LPS-induced NFAT activation in mouse and human DCs ( 64 ), signifying an atypical mechanism of Ca2 + mobilization leading to CN-NFAT activation in these cells.…”
Section: Nfat Signaling In Myeloid Immune Cells: Is This the Key Pathway Mediating Neutrophil Functions?mentioning
confidence: 99%
“…Some progress is already being made in this regard with the development of next-generation CNI, such as the VIVIT peptide, which selectively inhibits the calcineurin/NFAT interaction, but does not compromise calcineurin’s phosphatase activity ( 104 ). A recent study showed the potential of this peptide, conjugated to nanoparticles designed to target phagocytic cells, to dampen inflammation in a murine model of arthritis ( 64 ). Not only do such approaches hold direct therapeutic potential, but they may also prove invaluable as tools with which to discriminate the roles of CN-NFAT activation in specific cell types, including neutrophils.…”
Section: Future Perspectivesmentioning
confidence: 99%